Creep fracture of a nickel base single crystal superalloy along [011] orientation - SHUI Li; HU Zhuang-qi (工程科学学报)
The creep fracture behavior of a[011] oriented single crystal nickel base superalloy was investigated in the temperature range of 750 to 980℃ and the stress scope of 200 to 680 MPa. The fracture surfaces and longitudinal sections of crept specimens were examined by scanning electron microscopy(SEM). It is found that under different initial stresses at 750℃ and 870℃,creep cracks seem always to initiate at the γ'/γ interface on the interdendritic sub-boundary and propagate along the sub-boundary trace,and their cleavage planes expand along〈110〉and〈100〉on the(011) plane. But under different stresses at 980℃,creep cracks initiate at inherent casting pores and slowly propagate perpendicular to the axis of stress applied up to the final fast fracture. After observing the longitudinal sections of specimens crept under different stresses at 750℃ and 870℃,it is feasible for the area fraction of irregularγ' phase in the sub-boundary to characterize the creep damage level before collapsing of the superalloy along the[011]direction at the moderated and low temperatures.